2016
DOI: 10.12714/egejfas.2016.33.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Determination of households fish consumption structure and purchase behaviors in urban areas of Van

Abstract: Öz: Bu çalışma, Van ili kentsel alanda yaşayan hanelerin balık tüketim yapısı ve satın alma davranışlarını belirlemek amacıyla yapılmıştır. Araştırmanın ana materyalini Van İli kentsel alanda yaşayan 260 haneden anket yoluyla toplanan veriler oluşturmaktadır. Verilerin analizinde, frekans tabloları, Khi kare bağımsızlık testi ve sosyo-demografik bir takım kategorik değişkenlerin hanelerin balık tüketim miktarı ile arasındaki ilişki t ve f testleri ile test edilmiştir. Ankete katılan hanelerin %89.2'sinin balık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…It is stated that the frequency of fish consumption 1-2 times a week in individuals over the age of 20 in Türkiye is 17.2% (Anonymous, 2014). In local studies, it is also seen that it is consumed every fifteen days and one times a month (Terin et al, 2016;Selvi et al, 2022). According to the nutrition guide specific to Türkiye, it is stated that it is very important for children between the ages of 15-18 to consume 2 servings of fish per week in terms of growth and development (Anonymous, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is stated that the frequency of fish consumption 1-2 times a week in individuals over the age of 20 in Türkiye is 17.2% (Anonymous, 2014). In local studies, it is also seen that it is consumed every fifteen days and one times a month (Terin et al, 2016;Selvi et al, 2022). According to the nutrition guide specific to Türkiye, it is stated that it is very important for children between the ages of 15-18 to consume 2 servings of fish per week in terms of growth and development (Anonymous, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, it is stated that consumers prefer caughted and freshness or frozen, price, tasty, local fish market, fishbone (Terin et al, 2016;Bashimov, 2017;Sen and Sahin, 2017;Kirici et al, 2018;Sari et al, 2019;Rahman and Islam, 2020;Yigit et al, 2020). It is seen that while buying fish abroad, consumers were willing to pay more for domestic to imported production and fresh to frozen fish (Alam and Alfnes, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 18.73% of the surveyed consumers stated that they consumed fish only in summer season, while 22.84% stated that they consumed fish both in summer and in winter season. In previous studies reported that consumers consume fish meat maximum in winter seasons (Erdal and Esengun, 2008;Terin et al, 2016;Kizilaslan, 2019;Saka and Bulut, 2020).…”
Section: Consumers' Fish Consumption Status and Habitsmentioning
confidence: 99%